Participation of private sector companies in emerging capital markets: A study of capital markets in Tanzania. - Nangawe , Abbi Godfrey (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of Degree of Doctor of Philosophy of Mzumbe University.